Flexibilizing the Retirement Transition: Why, How and for Whom? Conceptual Clarifications, Institutional Arrangements and Potential Consequences - Scherger, Simone (Frontiers in Sociology, 2021)
In many countries, flexibilizing the retirement transition is seen as an innovative policy which may help to solve some of the problems ageing societies face. The paper aims at specifying what is or can be meant by flexibilizing the retirement transition. The proposed conceptual framework contributes to a better understanding of the potential individual and structural consequences of flexibilized retirement transitions. It spells out four dimensions based on which measures of flexibilization can be differentiated, compared and examined more closely: aggregate vs. individual flexibili-zation (the latter resulting in gradual retirement), the temporal form and reference of flexibilizing measures, accessibility and eligibility, and financial risks and costs resulting from flexible transitions to retirement. These dimensions of comparison are exemplified by referring to existing measures of retirement flexibilization, in particular wage subsidies and partial pensions. Based on the conceptual argument, some of the potential consequences of flexibilized retirement transitions are discussed critically and in particular with regard to questions of social inequalities. As these reflections show, the framework may also help to unpack the policy logic behind flexibilizing retirement transitions, and the very different interests it may serve.